Effect of annealing temperature on morphologies of metal organic framework derived NiFe2O4 for supercapacitor application. (August 2021) - Patil, P.D.; Shingte, S.R.; Karade, V.C.; Kim, J.H.; Dongale, T.D.; Mujawar, S.H.; Patil, A.M.; Patil, P.B.
Highlights: Metal organic framework (MOF) derived NiFe2 O4 (NFO) synthesized as electrode material in supercapacitors. Different morphologies such as threads, mesh-like structures, and grains were achieved at annealing temperatures of 460 °C, 500 °C, and 550 °C, respectively. The MOF derived NFO obtained by annealing at 500 °C (NFO500) exhibits mesoporous nature with a specific surface area of 38.17 m 2 g −1 . NFO 500 has a specific capacitance of 833 F g −1 at 0.25 A g −1 with 74% capacitance retention after 3000 cycles at 3 A g−1. NFO500 electrode has notable electrochemical performances in terms of specific energy and specific power (42 Wh kg −1 at 154 W kg −1 ). Abstract: The aim of this work is to obtain different morphologies of the metal organic framework (MOF) derived NiFe2 O4 (NFO) for supercapacitor application. The NFO samples were obtained by annealing solvothermaly synthesized NiFe2 MOF. The crystalline phase, morphology, particle size, and presence of functional groups of NFO were investigated by X-ray diffractometry (XRD), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), and Fourier transform infrared spectroscopy (FTIR), respectively. Moreover, chemical states, surface area, and pore size distribution of the optimized sample are evaluated by X-ray photoelectron spectroscopy (XPS) and surface area analyzer, respectively. The cubic spinel structured MOF derived NFO with different morphologies like threads, mesh-like structure, and grains were obtained at annealing temperatures of 460 °C, 500 °C, and 550 °C, respectively. FTIR analysis revealed the organic ligands decomposes with increasing annealing temperature. XPS analysis showed that MOF derived NFO prepared by annealing at 500 °C (NFO500) has Ni 2+, Fe 2+, and Fe 3+ states with some NiO impurities. Sharp edged rhombus nanoplates with interconnected mesh-like structure was observed for MOF derived NFO500. The synthesized MOF derived NFO500 electrode showed a mesoporous nature with a specific surface area of 38.17 m 2 g −1, which can be favourable for efficient charge transfer and high energy storage capability. The MOF derived NFO500 electrode exhibited a high specific capacitance of 833 F g −1 and specific energy of 42 Wh kg −1 at a specific power of 154 W kg −1 in 1 M KOH. After 3000 continuous cycles, NFO500 retained 74% capacitance at 3 A g −1 with 84% coulombic efficiency. The good electrochemical performance of MOF derived NFO500 compared to other samples is attributed to the mesh-like structure facilitating the diffusion of OH − ions into the electrode and the low charge-transfer resistance (2.7 Ω cm −2 ) between electrode and electrolyte interface. This study highlights the utility of modifying the morphologies of MOF derived nanostructures for energy storage applications. Graphical abstract: Image, graphical abstract